The Influence of Promotion and Price Fairness towards Customer Loyalty mediates by Customer Satisfaction on GoJek - Danty Adistya Artamevia Puteri Adji; Innocentius Bernarto (Dinasti Review, 2024)
This study aims to analyze the effect of Promotion and Price Fairness on Customer Loyalty, both directly and indirectly, through Customer Satisfaction as a mediating variable. The research focuses on GoJek users in Jabodetabek area to understand how promotional activities and pricing policies shape customer loyalty in the ride-hailing industry. The study employs a quantitative approach with a survey method, collecting data from 220 respondents. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that Promotion and Price Fairness have a significant positive effect on Customer Satisfaction and Customer Loyalty. Furthermore, Customer Satisfaction serves as a key mediating variable that amplifies the impact of Promotion and Price Fairness on Customer Loyalty. The findings highlight the importance of effective promotional strategies and fair pricing policies in fostering customer satisfaction and loyalty in competitive digital service ecosystems like ride-hailing. The study concludes that enhancing Customer Satisfaction through these variables is critical for GoJek to strengthen customer retention and sustain a competitive advantage in the market.